Are Citizens Willing to Reduce Public Debt? Beliefs, Information and Policy Preferences - Massimo Bordignon; Nicolò Gatti; Gilberto Turati (CESifo GmbH, 2025)
This paper investigates how raising awareness of public debt sustainability affects individual attitudes toward debt reduction and fiscal policy preferences. Using a survey experiment on a representative sample of the Italian population, we randomly assign objective information about government debt to citizens, who become more sensitive to the risks of tax increases, spending cuts, and imbalances for future generations. We find no effect on the perception of debt reduction as an urgent policy priority. While remaining highly averse to any tax increase, treated respondents support spending cuts (but not in education and health care) as a policy to reduce the debt burden. We also show that subjects with distorted beliefs about government debt are no more responsive to the information treatment than subjects with correct beliefs, shedding light on the challenges of building a voting majority for debt-stabilizing policies.
Keywords: H63; H31; D83; 330; public debt; fiscal policies; beliefs; information